Peripheral Mechanisms of Ischemic Myalgia - Queme, Luis F.; Ross, Jessica L.; Jankowski, Michael P. (Frontiers in Cellular Neuroscience, 2017)
Musculoskeletal pain due to ischemia is present in a variety of clinical conditions including peripheral vascular disease (PVD), sickle cell disease (SCD), complex regional pain syndrome (CRPS), and even fibromyalgia (FM). The clinical features associated with deep tissue ischemia are unique because although the subjective description of pain is common to other forms of myalgia, patients with ischemic muscle pain often respond poorly to conventional analgesic therapies. Moreover, these patients also display increased cardiovascular responses to muscle contraction, which often leads to exercise intolerance or exacerbation of underlying cardiovascular conditions. This suggests that the mechanisms of myalgia development and the role of altered cardiovascular function under conditions of ischemia may be distinct compared to other injuries/diseases of the muscles. It is widely accepted that group III and IV muscle afferents play an important role in the development of pain due to ischemia. These same muscle afferents also form the sensory component of the exercise pressor reflex (EPR), which is the increase in heart rate and blood pressure experienced after muscle contraction. Studies suggest that afferent sensitization after ischemia depends on interactions between purinergic (P2X and P2Y) receptors, transient receptor potential (TRP) channels, and acid sensing ion channels (ASICs) in individual populations of peripheral sensory neurons. Specific alterations in primary afferent function through these receptor mechanisms correlate with increased pain related behaviors and altered EPRs. Recent evidence suggests that factors within the muscles during ischemic conditions including upregulation of growth factors and cytokines, and microvascular changes may be linked to the overexpression of these different receptor molecules in the dorsal root ganglia (DRG) that in turn modulate pain and sympathetic reflexes. In this review, we will discuss the peripheral mechanisms involved in the development of ischemic myalgia and the role that primary sensory neurons play in EPR modulation.